2014
DOI: 10.1177/1357633x14524156
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of research into frequent callers to crisis helplines

Abstract: SummaryWe conducted a systematic review of research into callers making multiple calls to crisis helplines. Two databases were searched, identifying 561 articles from 1960 until 2012, of which 63 were relevant. Twenty-one articles from 19 separate studies presented empirical data about callers making multiple calls to crisis helplines. Of the 19 studies, three were intervention studies, five were surveys of callers and 11 were call record audits. Most studies were conducted in the USA and defined frequent call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
74
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 27 publications
(216 reference statements)
10
74
3
2
Order By: Relevance
“…The challenge the TNs experienced with FCs in the present study is congruent with the study by Holmström et al (), where FCs constituted a challenge for TNs and often comprised the caller's worries and anxieties. Furthermore, in the background it is described that in several studies the FCs were more likely to have psychiatric comorbidity (Corral et al, ; Edwards et al, ; Fisher et al, ; Liu et al, ; Middleton et al, ; Pirkis et al, ; Ramors‐Rivers et al, ; Spittal et al, ), which also seems to be the case in the present study according to these TNs. It has previously been shown that there is a positive relationship between expressions of concern by the caller and disapproval by the nurse (Ernesäter, Engström, Winblad, Rahmqvist, & Holmström, ).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The challenge the TNs experienced with FCs in the present study is congruent with the study by Holmström et al (), where FCs constituted a challenge for TNs and often comprised the caller's worries and anxieties. Furthermore, in the background it is described that in several studies the FCs were more likely to have psychiatric comorbidity (Corral et al, ; Edwards et al, ; Fisher et al, ; Liu et al, ; Middleton et al, ; Pirkis et al, ; Ramors‐Rivers et al, ; Spittal et al, ), which also seems to be the case in the present study according to these TNs. It has previously been shown that there is a positive relationship between expressions of concern by the caller and disapproval by the nurse (Ernesäter, Engström, Winblad, Rahmqvist, & Holmström, ).…”
Section: Discussionsupporting
confidence: 76%
“…A study performed in Sweden with TNs in primary healthcare settings indicated that frequent callers (FCs’) calls constitute a challenge for TNs and are often comprised of the caller's worries and anxieties along with their physical symptoms (Holmström, Krantz, Karacagil, & Sundler, ). The phenomenon of callers making multiple calls has been described in the literature in different terms, such as frequent, chronic, or repeat callers (Middleton, Gunn, Bassilos, & Pirkis, ). The number of calls made to meet the criterion for being a FC also varies (Middleton et al, ; Scott, Strickland, Warner, & Dawson, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…If a caller made less than answered N calls, we collected that lower number of calls. The values of N cascaded through the sequence: 2,4,8,16,24,32,48,64,256,1024,2048,4096,8192. We hoped that low values of N would reasonably suffice overall.…”
Section: Models Cascadementioning
confidence: 99%